Aras Design and Multimedia Centre (ADMC): it's pricing strategy for video internet market training. Issue 3 (18th October 2016) - Basiruddin, Rohaida; Tobi, Siti Uzairiah Mohd.; Quoquab, Farzana
Abstract : Subject area: Managerial Accounting, Strategic Marketing. More specifically, cost behavior, cost estimation, cost prediction, cost-volume-profit (CVP) analysis, contribution income statement and pricing/promotional strategy. Study level/applicability: This case is suitable to be used in advanced undergraduate level. Case overview: This case demonstrates the issues relating to pricing strategy of "Video Internet Marketing Training". Diyana Tahir and her husband, Abdul Rahim Abdul Shukor, established Aras Design & Multimedia Centre (ADMC) on January 17, 2009. The main office was located at Kuala Lumpur. Diyana was a well-known name in the field of internet video marketing training. In its early years, ADMC's operation was limited to providing printing and graphic design services and offering printing materials for photocopy. However, with the passage of time, the company began to expand its services and offerings. At the beginning of 2010, ADMC offered editing facilities and services for video and multimedia in addition to its core services. As a unique marketing strategy, Diyana offered RM30 as the basic training fee for each participant, which was equivalent to RM470 value offered. In this way, she attracted customers to take part in further advanced level training that was conducted by ADMC. However, she felt that the number of participant to take advanced training was not satisfactory. She thought that it happened perhaps due to the fact that the participants were not much committed to the course since it was offered at a nominal price. Furthermore, she realized that the cost of providing such training had risen in the past six months. Currently, ADMC suffered losses in three consecutive months, and they really needed enough cash to sustain. As such, Diyana was thinking to reconsider the offered course fees whether to increase it. She was in a rush to make a decision to propose the new course fee in the monthly meeting with management committee at the end of April 2013. Expected learning outcomes: Using this case, students can learn how a small-scale company can strategize its pricing strategy to survive in the highly competitive online market. The objectives of using this case are as follows: to help students in understanding the interrelationships between CVP in organization that can be used for future planning and decision-making; to be able to identify the cost structure of the basic training course (e.g. fixed and variable costs), determine the contribution margin, break-even point and prepare the contribution income statement that highlighting cost behavior; to help students to think critically while setting the price for the offered services; to develop students' ability in analyzing the existing situation to come up with a viable and effective solution; to assist students in taking the right move in a right time; to broaden students' views and understanding in considering the monetary aspect along with the human aspect in formulating an effective marketing strategy; to develop students' understanding of the way to retain and attract customers through innovative pricing strategy; and to make students aware that innovation is the key to business success. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject codes: CSS 1: Accounting and Finance.